2021
DOI: 10.1002/ijgo.13489
|View full text |Cite
|
Sign up to set email alerts
|

Aortic isthmus Doppler in normal and small‐for‐gestational‐age fetuses and its association with prediction of adverse perinatal outcome

Abstract: Objective To establish reference ranges for aortic isthmus Doppler indices in appropriate‐for‐gestational‐age (AGA) fetusesand to evaluate its association with perinatal outcome in small‐for‐gestational‐age (SGA) fetuses. Methods Prospective cohort observational study in which 30 pregnant women with SGA fetuses and 60 women with AGA fetuses were recruited from the prenatal clinic of the hospital. The AGA group was eventually followed from 24 weeks by 4‐weekly Doppler assessment, and the SGA group was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Sharma et al evaluated 30 pregnant women with small for gestational age (SGA) foetuses and found the AoI PI values to be significantly higher in the SGA group than in the control group. They observed that AoI assessment seems to provide beneficial information for monitoring small foetuses (24). There are studies in which the sensitivity and clinical benefit of AoI Doppler PI values in FGR could not be found, especially for late-onset FGR (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al evaluated 30 pregnant women with small for gestational age (SGA) foetuses and found the AoI PI values to be significantly higher in the SGA group than in the control group. They observed that AoI assessment seems to provide beneficial information for monitoring small foetuses (24). There are studies in which the sensitivity and clinical benefit of AoI Doppler PI values in FGR could not be found, especially for late-onset FGR (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The left ventricle (LV) perfuses the coronary and brachiocephalic circulations, while the right ventricle (RV) the subdiaphragmatic circulation and placenta 3,4 . Retrograde flow (RF) may occur in the aortic isthmus (AI), the segment between the left subclavian artery and the ductus arteriosus (DA) insertion in the descending aorta 5–10 in fetuses with intra‐uterine growth restriction (IUGR), small for gestational age (SGA), 10–27 and some congenital heart disease (CHD), 28–30 such as transposition of great artery (TGA). However, RF in various fetal heart disease (FHD), including abnormalities in heart structure and function, and its association with flow variables has not been systematically studied 8,21 …”
Section: Introductionmentioning
confidence: 99%